INTERPRETASI SISTEM PANAS BUMI WAY UMPU MENGGUNAKAN DATA GRAVITASI - , MUKHAMAD FARDIAN HATARI SATRIA, Drs. Imam Suyanto, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research using the gravity method applied in Way Umpu geothermal area to identify geothermal system. Regional anomalies and the residual anomalies were separated using upward continuation method with an altitude of 1000 meters. Subsurface structure modelling was made by the residual anomalies. Then they were correlated with the geological data and the fault analysis result using the second vertical derivative (SVD). The model shows that the lithology consist of basaltic lava with density 2,9 gr/cc. It was the result of the Pungur vulcano activities. Basaltic breccia with density 2,65 gr/cc is interpreted as a geothermal reservoir, andesite lava with density 2,8 gr/cc is analyzed as the result of the activity of Mt. Remas which plays as the cap rock and andesite breccia with density 2,6 gr/cc.That lithology are being covered by alluvial rock with density 1,9 gr/cc Keyword : gravity method, SVD, modelling, geothermal